Analisis Karakteristik Wirausaha, Jaringan Usaha dan Persaingan Usaha Terhadap Perkembangan UMKM Di Kecamatann Kota Kefamenanu - Pangastuti, Margareta Diana; Marce Sherly Kase; Hezron Tri Muki (Ekopem: Jurnal Ekonomi Pembangunan, 2025)
The activities of Micro, Small and medium enterprises (MSMEs) is one way that regional creative products can be known and provide business opportunities for business actors. In addition, the role of Micro, Small and medium enterprises (MSMEs) is considered very important in order to increase per capita income and improve the economy of a region. Micro, Small and medium enterprises (MSMEs) is one of the business fields that can develop and be consistent in the national economy. The problem of this research is: do the characteristics of entrepreneurship (X1), Business Network (X₂) and business competition (x₂) jointly affect the development of MSMEs in kefamenanu City district? The objectives to be achieved in this study: to determine the effect of the characteristics of entrepreneurship (X1), Business Network (X₂) and business competition (x₂) together on the development of MSMEs (Y) in the district of kefamenanu city. Technical data analysis used is simple linear regression analysis and multiple linear regression . Based on the results of the data processing, shows that the results of simple linear regression analysis, X1 to y significant effect, X2 to Y significant effect, X3 to Y significant effect, and the results of multiple linear regression analysis, (X1), (X₂) and (x₂) to (Y) have a significant effect. Keywords: entrepreneurial characteristics, Business Network, Business Competition and MSME Development